Investigation of application efficiency of two rows blades in the fan vent installation - Терещенко, Ю. М.; Панін, В. В.; Гуз, С. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
Experimental results of two-row blade rims for increasing pressure fans ventilation systems ejector type are shown